Efektivitas Audio Flash Card dan Teman Ajar Isyarat terhadap Pengetahuan Protokol Kesehatan Covid-19 pada Anak Disabilitas di Sekolah Luar Biasa Alhidayah Padang - Milletesya Govanda; Yulizawati Yulizawati; Hardisman Hardisman (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2022)
In a pandemic situation, challenges are even more significant where there is limited space for movement and need strict assistance for children with disabilities to prevent Covid-19. A common problem faced by children with disabilities is that they cannot understand abstract and verbal things, even though verbal skills are very much needed in implementing the Covid-19 health protocol. Children with disabilities need assistive devices in the form of visual media so that they can more easily apply health protocols through their senses. In Padang, West Sumatra, the highest Covid-19 cases were in Kuranji Subdistric. For this reason, the implementing team provided education regarding the Covid-19 health protocol to children with disabilities at the Alhidayah Special School using the Audio Flash Card game method and Friends Teaching Signs. It was done so that children with disabilities were hight interested in participating. The results show that the education provided was more effective with the Audio Flash Card game method and Friends Teaching Signs because, for children with disabilities, this method is more fun and easier to understand. Thus, this method should be applied and combined in the educational process so that children with disabilities can easily understand the material presented.